Grid-connected distributed renewable energy generation systems: Power quality issues, and mitigation techniques – A review - Etanya, Tiku Fidelis; Tsafack, Pierre; Ngwashi, Divine Khan (Energy reports, 2025)
The rapid increase in power consumption, limited generation capacities, rapid depletion of traditional energy sources, and adverse ecological effects have increased research interest in distributed generation (DG) systems dominated by renewable energy (RE) sources. Power system operators are looking for proven solutions to enhance power quality (PQ) and raise the overall penetration of renewable energy sources in grid-connected systems. However, because most renewable energy sources are intermittent such as wind power or solar PV, power quality issues in the generation network have rapidly increased. As the prevalence of renewable energy sources increases, keeping a permissible level of power quality is difficult. These power quality issues often manifest themselves in voltage and frequency fluctuations in the power system. This review focuses on power quality issues in distributed renewable energy generation (DREG) systems, grid-connected DREG systems, and mitigating techniques.